Association between Morphological Changes of Nail and Nail Arsenic Level in Patients with Arsenicosis - Shafiquzzaman, Md; Jahan, MK; Rahman, MM; Islam, MT; Miah, MA; Kamal, M; Islam, MM; Choudhury, AM; Chowdhury, SA; Mohammad, N (Mymensingh Medical Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Mymensingh Med J. 2009 Jan;18(1):27-30. The abstract of this article is available on the PubMed website